Vol. 51 : Information Technologies in Science, Management, Social Sphere and Medicine (ITSMSSM 2016): III International Scientific Conference, May 23-26, 2016, Tomsk, Russia; [proceedings]; Advances in Computer Science Research - Berestneva O. G. Olga Grigorievna; Tikhomirov A. Alexei; Trufanov A. Andrey (2016, 2016)
Title screen